Fear in Andalusian poetry (Journal of the College of Basic Education, 2022)
Thinking about death and being afraid of it was something that haunts people everywhere and at all times.As an indispensable end to life, and Eternity has been exalted to those who seek it.” However, fear sometimes becomes feara disease that has no cure; It spoils life and makes it difficult, and the Muslim Arabs in Andalusia faced fearof its various types; Death and common torment were the broadest in them, as evidenced by their poetry.This poetry included three directions of fear; The first is the fear of believing Muslims from tormentGod Almighty hereafter. The second is the fear of sinners from the punishment of the sultans and rulers in this worldAnd the third is the fear of the owners of the world of leaving it while they are keen on its pleasures, pleasures and joysAnd they want more of it.